Dermatite digital bovina: etiologia, reservatórios e rotas de transmissão - Leandro Silva de Andrade (2017)
Digital Dermatitis (DD) is one of the major diseases of the bovine locomotor system that leads animals to claudication and although bacteria of the genus Treponema are consistently identified in DD-damaged tissues, the definitive etiology of this polymicrobial disease has not yet been fully understood. In order to elucidate the etiology of this disease and its possible transmission routes within a dairy farm, 37 biopsies of animals affected by DD were performed and 13 samples of rumen fluid and 13 samples of cows' feces were collected. Specific areas of the property were also collected, such as the material accumulated around the drinking fountain, feeding lane, milking waiting room, footwash and footbath and to compare the microbiome found in lesions with healthy skin, three biopsies of Skin lesions adjacent to the lesion. For the analysis of the microbiomas of DD and whole skin, the in situ Fluorescent Hybridization (FISH) molecular techniques and new generation sequencing were used, and the ruminal fluid, feces and environment samples were analyzed by the new generation sequencing method. The bacterial presence was found in the FISH technique in 96.55% of the lesions and the bacteria of the genus Treponema were the most prevalent, being present in 93.55%. Dichelobacter nodosus was present in 58.06%; Fusobacterium necrophorum in 35.49% and Porphyromonas levii in 33.43%. The bacteria of the genus Treponema were the ones that had higher density in the analyzed samples, followed by Dichelobacter nodosus; Fusobacterium necrophorum and Porphyromonas levii. There were seven different phylotypes in DD samples: T. pedis, T. refringes, T. phagedenis, T. medium and some phylo- types that were not previously cultivated and were classified in this study as: PT18, PT13 and PT3, being T. phagedenis and T. pedis species found in higher densities in the lesions. By the new generation sequencing technique Treponemes were present in 68.6% of the lesions, Porphyromonas in 91.4%, Mycoplasma in 85.7%, Helicococcus in 74.4%, Corynebacterium in 60%, Fusobacterium in 45.7% %, Dichelobacter in 40%, and Alloiococcus in 17.1%, and phylotypes were also found that were not previously identified in the literature. In the samples of ruminal fluid, feces and environment Treponemas were found, but in low proportions and of the Treponemas found in these places the most prevalent ones are still unknown in the literature. The data found in this study support the concept that the etiology of DD is mainly "multitreponemal" and polymicrobial, where several agents may act synergistically with treponemas to cause DD injury. Bacteria of the genus Treponema were also found in the rumen, feces and environmental samples of the property, mainly Treponemas that have not yet been classified in the literature. We suggest that the microbiota of the gastrointestinal tract and the environment of the farm can act as reservoirs of bacteria involved in the pathogenesis of DD. Further research is needed on the actual potential of gastrointestinal tract function as a reservoir for pathogens that lead to the development of the lesion.